Deteksi Faktor Risiko Penyakit Tidak Menular melalui Pos Pembinaan Terpadu Warga Sehat di Era Pandemi Covid-19 - Sulistyaningsih Sulistyaningsih; Tri Hapsari Listyaningrum (Universitas Muhammadiyah Surakarta, 2021)
Non-Communicable Diseases (NCD) are a serious threat during the Covid-19 pandemic because they are a vulnerable group. Most of the community’s behavior is a risk factor for NCD, smoking habits, eating less fruits and vegetables, and less physical activity. RT 1 RW 7 Mejing Wetan, Ambarktawang, Gamping, Sleman have community groups that hold regular meetings every month, but there is no forum for NCD risk factor detection activities. The purpose of community service activities is to form Posbindu NCD so that it can help NCD risk factors so that they control NCD in the era of the Covid-19 pandemic. The implementation method of compiling the NCD risk factor detection book, outreach to community leaders, ordering the management, cadre training, preparing infrastructure and implementing Posbindu and monitoring sustainability. Activities have been carried out from August-December 2020. The results of the activity are trained cadres, a pocket book of NCD risk factors, the formation of the Posbindu WARAS (Warga Sehat) management, and the implementation of Posbindu with the Covid-19 health protocol so that it can provide NCD risk factors. The conclusion is that Posbindu NCD can be formed and can carry out activities regularly every month has successfully detected NCD risk factors.Posbindu cadres are asked to continue Posbindu activities regularly every month and can increase activities to increase community participation.